Extraction and Analysis of Depth and Angular Effects on Reflectance, SNR, and BER in Underwater Optical Wireless Communication Systems (Architecture Image Studies, 2026)
Underwater optical wireless communication (UWOC) has emerged as a promising high-capacity alternative to conventional underwater acoustic communication systems, While acoustic communication supports long transmission ranges, it suffers from limited data rates, high latency, and sensitivity to ambient noise. In contrast, UWOC systems operate in the visible blue–green optical spectrum, enabling very high data rates, low propagation delay, and enhanced security, which makes them well suited for short- and medium-range underwater applications, Nevertheless, the performance of UWOC links is highly dependent on both environmental conditions and system design parameters.This paper presents an analytical investigation of the effects of beam divergence angle, water temperature, salinity, and theoretical depth on UWOC system performance, Key performance metrics such as optical reflectance, signal-to-noise ratio (SNR), and bit error rate (BER) are examined in detail, Beam divergence angle is identified as a critical factor influencing received optical power, Narrow divergence angles improve power concentration and SNR but require accurate alignment, whereas wider divergence angles enhance robustness to misalignment at the expense of increased geometric spreading, absorption, and scattering losses, leading to BER degradation.The study also analyzes the impact of environmental parameters. Variations in temperature and salinity alter the refractive index and optical attenuation characteristics of water, thereby affecting signal propagation and noise levels, Higher salinity and temperature gradients generally increase attenuation and reduce communication reliability, particularly in deeper water conditions.Additionally, a theoretical depth-impact model is introduced to evaluate the limitations imposed by increasing depth, The results demonstrate that cumulative optical losses and background noise significantly restrict UWOC link performance with depth, Overall, the findings provide useful guidelines for the design and optimization of reliable UWOC systems under diverse underwater environments.